Ofídios da Amazônia XVIII - o gênero Chironius Fitzinger, na Amazônia Oriental. (Ophidia: Colubridae) - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1982)
Contribution to the knowledge of the species of Chironlus fitzinger, Eastern Amazonia, supported in 379 copies from the collections of the Goeldi Museum. The analysis is complemented with other data obtained in specimens from Roraima, Amazonas and north of Mato Grosso, preserved in the Goeldi Museum and the National Museum of Rio de Janeiro. The goal is to reassess the species C. scurrulus (Wagler), C. fuscus (Linnaeus), C. exoletus (Linnaeus), C. carinatus (Linnaeus), C. flavolineatus (Boettger) and C.
Keywords: Chironlus Fitzinger; Amazônia Oriental; Museu Emílio Goeldi; Roraima - Estado; Amazonas - Estado; Mato Grosso - Estado; Museu Nacional; C. scurrulus (Wagler); C. fuscus (Linnaeus); C. exoletus (Linnaeus); C. carinatus (Linnaeus); C. flavolineatus (Boettger); C. multiventris Schmidt & Walker; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA